Работа на микроЭВМ - Александриди Т. М. Тамара Миновна; Иванов А. И. Алексей Игоревич; Каганов Ю. Л. Юрий Львович; Покрас Ю. Л. Юрий Львович (Москва, Финансы и статистика, 1989)
Авт. указаны на обороте тит. л.